Globalization, agricultural markets and mass migration: Italy, 1881-1912 - Gray, Rowena; Narciso, Gaia; Tortorici, Gaspare (Explorations in economic history, 2019)
Despite the significant attention paid to the current consequences of globalization for migration behavior, there are few historical accounts of the effect of commodity market integration at the local level. We set our paper within the context of the first globalization era, when migration flows were largely unregulated, and highlight how exogenous shocks in agricultural commodity prices influenced international migration flows from Italian provinces between 1881 and 1912. To do this, we construct an index of global price exposure based on the initial provincial agricultural production structures. Our analysis quantifies the contribution of globalization-induced agricultural-price shocks to migration decisions, alongside more traditional explanatory factors such as migrant networks and landholding systems. We find evidence that agricultural-price shocks are positively related to the propensity to migrate, as migration tended to increase in proportion with agricultural commodity prices. This result suggests that liquidity constraints were binding until agricultural incomes reached a certain threshold. These findings can inform our understanding of present-day migration responses in developing countries in the face of even more rapid globalization but higher barriers to legal migration.